Tl(I) sorption behavior on birnessite and its implications for mineral structural changes. (1st March 2019) - Cruz-Hernández, Yusniel; Villalobos, Mario; Marcus, Matthew A.; Pi-Puig, Teresa; Zanella, Rodolfo; Martínez-Villegas, Nadia
Abstract: Thallium is the most toxic regulated metallic ion in soil and water. Previous work in soil samples contaminated by metallurgical wastes has revealed a very high correlation between extracted Tl and Mn in the reducible mineral fractions, which suggests a high geochemical affinity between Tl and Mn oxides, once Tl has been released from the primary minerals it is originally associated with (aluminosilicates and sulfides). The goal of the present work was to determine the behavior and mechanisms of thallium (I) sorption on Mn(IV)-birnessites, focusing on expanding the conditions previously investigated, by using two synthetic poorly-crystalline preparations of this mineral that are the closest analogs to biologically-produced Mn oxides, but differ greatly in their particle sizes; and by testing the effects of a wide range of pH values and Tl(I) concentrations, to simulate a large variability in geochemical conditions. To achieve this, we performed Tl(I) sorption isotherms on clean preparations of both birnessites at three different pH values (4, 6 and 8) and X ray Absorption Spectroscopy (XAS), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM) and Specific Surface Area (SSA) analyses on selected samples. Thallium (I) sorption to the birnessites consists of a prevailing irreversible oxidation mechanism, with retention of the Tl(III) produced, mainly over vacant layer sites, and eventual formation of the mineral avicennite (Tl2 O3 ) at high loadings and pH. Thallium (I) was increasingly sorbed/oxidized at all pH values, but its extent increased as pH was raised, contrary to what the redox reaction suggests, where protons contribute as reacting agents. The sorption/oxidation reaction was also independent of the birnessite initial particle size or vacancy content. This strongly suggests that the net negative electrostatic charge of the birnessite plays a major role in the reaction, and therefore, the sorption part of the mechanism is the limiting and prevailing step of the overall process; however, since Tl(I) enters into the mineral structure and may potentially access all internal Mn(IV) available, the redox reaction appears to be boundless, showing extremely high capacities for Tl(I) oxidation. Finally, at high concentrations of the Tl(III) formed, and apparently coinciding with the formation of avicennite (Tl2 O3 ), a general delamination of the birnessite layered structure was provoked adding to its gradual dissolution.